Experience matters: a systematic review and research agenda on predictors to buy sustainable fashion - Toebast-Wensink, Annuska; van den Broek, Karlijn L.; Timmerman, Tijs; Hekkert, Marko P. (Frontiers in Sustainability, 2025)
IntroductionWhile consumers have become increasingly aware of the need for sustainability in fashion, many do not translate their intention to purchase sustainable fashion into actual behavior. Insights can be gained from those who have successfully transitioned from intention to behavior (i.e., experienced sustainable fashion consumers). Despite a substantial body of literature exploring predictors of sustainable fashion purchasing, a comprehensive view on how predictors of sustainable fashion purchasing vary between consumers with and without sustainable fashion experience is lacking.MethodsThis paper reports a systematic literature review, analyzing 100 empirical articles on predictors of sustainable fashion purchasing among consumer samples with and without purchasing experience, identified from the Web of Science and Scopus databases.ResultsThe review revealed that (I) environmental cognition, such as environmental awareness, knowledge, and perceived consumer effectiveness, occurs most frequently as significant predictors for both groups; (II) subjective norms occur more frequently as significant predictors for general consumers than for experienced consumers; (III) habits occur more frequently as significant predictors for experienced consumers compared to general consumers; and (IV) experience can shift barriers into motivators.DiscussionThis review highlights experience as a transformative factor for sustainable fashion purchasing, showing that as consumers gain experience, their attitudes evolve and influence decisions. It also emphasizes the potential of goal framing, suggesting that effective goal frames can encourage initial sustainable fashion purchases among general consumers. From a practical perspective, this review suggests that marketers and retailers should employ distinct tactics for first-time and experienced sustainable fashion consumers to effectively engage each group and enhance purchasing.